Letter from R.E. Preston to Margaret M. Booth, February 19, 1890 - Preston, Robert E., 1836–1911 (1890)
Letter from Robert E. Preston (1836-1911), of the United States Mint Bureau, to Margaret M. Booth née Cardeza informing her that he is not having success getting a bill to relieve her husband's estate introduced through Congress. Preston describes the hectic activity in Congress and concludes by suggesting that Margaret consider hiring an attorney to represent her in the courts.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Preston, Robert E., 1836–1911; United States Mint; Mint of the United States